Robust estimation of wage dispersion with censored data: An application to occupational earnings risk and risk attitudes - Daniel Pollmann; Thomas Dohmen; Franz C. Palm (Institute for the Study of Labor (IZA), 2012)
We present a semiparametric method to estimate group-level dispersion, which is particularly effective in the presence of censored data. We apply this procedure to obtain measures of occupation-specific wage dispersion using top-coded administrative wage data from the German IAB Employment Sample (IABS). We then relate these robust measures of earnings risk to the risk attitudes of individuals working in these occupations. We find that willingness to take risk is positively correlated with the wage dispersion of an individual's occupation.
urn:nbn:de:101:1-201207127137
Keywords: C14; C21; C24; J24; J31; D01; D81; 330; dispersion estimation; earnings risk; censoring; quantile regression; occupational choice; sorting; risk preferences; SOEP; IABS; Beruf; Lohnstruktur; Risiko; Berufswahl; Risikopräferenz; Schätzung; Deutschland